PERBEDAAN SKOR WORK ENGAGEMENT PADA GURU YANG BERSERTIFIKASI DENGAN GURU YANG BELUM BERSERTIFIKASI DI SMP NEGERI SE-KECAMATAN DENPASAR UTARA - Aditya, Gede Andi; Adiputra, I Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2015)
Optimum performance is achieved when teacher has been engaged with his or her work. Teacher will not feel forced to run his or her job demand and even tend to give more than his or her job demand. These are ideal condition that must be maintained in teacher profession. Efforts to do so teacher engaged with his or her work is to provide an acknowledgment and appreciation.  It can be seen from one of the government's regulations implementing teacher certification.  Observational studies have been conducted with a cross-sectional analytical approach to the teacher at SMP Negeri inNorth District of Denpasar with a sample of 147 peoples. Data were analyzed with the Mann-Whitney test with a significance level of 0.05. Research data obtained an average scores of work engagement on the certified teachers is 86.23 + 8,31 while the average scores of work engagement on uncertified teachers is 79.25 + 11,93. Comparability of test results p = 0.003, showing that the average scores of work engagement among certified teachers and uncertified teachers significantly different (p <0.05). It can be said certification is one of the variables that affect the work engagement on teacher. It was concluded that there are differences in the average scores of work engagement oncertified teacher with uncertified teacher, where work engagement scores on certified teacher is higher than uncertified teacher. It is recommended for government to certify all teachers in Indonesia.
Keywords: Teacher, Certification, Work Engagement